THE INFLUENCE OF JOB MARKET CONSIDERATIONS, CAREER PATH, FINANCIAL REWARDS, AND MOTIVATION ON ACCOUNTING STUDENTS’ CAREER CHOICE AS PUBLIC ACCOUNTANTS - Resta Nur Imani; Yuli Novitasari; Zahra Malinda Putri (Yayasan Education and Social Center, 2026)
Despite the increasing demand for public accountants, the interest of accounting students in pursuing careers in this profession remains relatively low. This condition indicates that various factors may influence students’ career decisions in the accounting profession. This study aims to analyze the influence of job market considerations, career path, financial rewards, and motivation on accounting students’ career choice as public accountants. This study employed a quantitative approach using a saturated sampling technique, involving 40 students from the Accounting Study Program at Universitas Sains Indonesia from the 2021-2022 cohorts as respondents. The data were analyzed using multiple linear regression with IBM SPSS Statistics version 27. The results showed that partially, career path, financial rewards, and motivation showed positive but insignificant effects on students’ career choice as public accountants. However, simultaneously, job market considerations, career path, financial rewards, and motivation significantly influenced accounting students’ career choice as public accountants, with a coefficient of determination of 87.7%. These findings highlight the importance of providing comprehensive job market information and strengthening career education strategies by higher education institutions and professional organizations to enhance students’ interest in the public accounting profession.